Antichlamydial Dimeric Indole Derivatives from Marine Actinomycete Rubrobacter radiotolerans - Li, Jian Lin; Chen, Dandan; Huang, Lei; Ni, Min; Zhao, Yu; Fan, Huizhou; Bao, Xiaofeng (Planta Medica, 2017)
Chlamydiae are widely distributed pathogens of human populations, which can lead to serious reproductive and other health problems. In our search for novel antichlamydial metabolites from marine derived-microorganisms, one new (1) and two known (2, 3) dimeric indole derivatives were isolated from the sponge-derived actinomycete Rubrobacter radiotolerans. The chemical structures of these metabolites were elucidated by NMR spectroscopic data as well as CD calculations. All three metabolites suppressed chlamydial growth in a concentration-dependent manner. Among them, compound 1 exhibited the most effective antichlamydial activity with IC50 values of 46.6 ~ 96.4 µM in the production of infectious progeny. Compounds appeared to target the mid-stage of the chlamydial developmental cycle by interfering with reticular body replication, but not directly inactivating the infectious elementary body.
Keywords: Chlamydia; dimeric indole; sponges; actinomycete; Rubrobacter radiotolerans; antichlamydial